Building a Practice-Based Research Agenda for Wildfire Smoke and Health: A Report of the 2018 Washington Wildfire Smoke Risk Communication Stakeholder Synthesis Symposium - Nicole A. Errett (International Journal of Environmental Research and Public Health, 2019)
Background: As climate change is expected to result in more frequent, larger fires and associated smoke impacts, creating and sustaining wildfire smoke-resilient communities is an urgent public health priority. Following two summers of persistent and extreme wildfire smoke events in Washington state, the need for additional research on wildfire smoke health impacts, risk communication, and risk reduction, and an associated greater coordination between researcher and practitioner communities, is of paramount importance. Objectives: On 30 October 2018, the University of Washington hosted a Wildfire Smoke Risk Communication Stakeholder Synthesis Symposium in Seattle, Washington. The goals of the symposium were to identify and prioritize practice-based information gaps necessary to promote effective wildfire smoke risk communication and risk reduction across Washington state, foster collaboration among practitioners and academics to address information gaps using research, and provide regional stakeholders with access to the best available health and climate science about current and future wildfire risks. Methods: Seventy-six Washington state practitioners and academics with relevant professional responsibilities or expertise in wildfire smoke and health engaged in small group discussions using the “World Café Method” to identify practice-relevant research needs related to wildfire smoke and health. Notes from each discussion were coded and qualitatively analyzed using a content analysis approach. Discussion: Washington state’s public health and air quality practitioners need additional evidence to communicate and reduce wildfire smoke risk. Exposure, health risk, risk communication, behavior change and interventions, and legal and policy research needs were identified, along with the need to develop research infrastructure to support wildfire smoke and health science. Practice-relevant, collaborative research should be prioritized to address this increasing health threat.